An electron-impact cross section data set (10 eV–1 keV) of DNA constituents based on consistent experimental data: A requisite for Monte Carlo simulations. (January 2017) - Bug, Marion U.; Yong Baek, Woon; Rabus, Hans; Villagrasa, Carmen; Meylan, Sylvain; Rosenfeld, Anatoly B.
Abstract: This work provides the first cross section data set of DNA constituents for an impact of electrons in the energy range between about 10 eV and 1 keV on a DNA target. The data set is designed for an implementation in Monte Carlo simulations and consists of model functions, taking into account elastic scattering, ionization and excitation interactions with the DNA constituents tetrahydrofuran, trimethylphosphate, pyrimidine and purine. It was developed on the basis of experimentally determined absolute differential and total scattering cross sections in accordance with the available literature data. The data set will be available in the Geant4-DNA toolkit to allow secondary electron transport in a DNA-like medium down to the ionization threshold. Abstract : Highlights: Cross section data set of DNA constituents for secondary electron-impact. Based on absolute experimental differential and total scattering cross sections. Suitable for implementation in track structure simulations.